Habitat preference and spatial distribution model of threatened species Saurauia microphylla in Mt. Slamet, Central Java, Indonesia - Hendra Helmanto; NISYAWATI; IYAN ROBIANSYAH; RIZMOON NURUL ZULKARNAEN; NABELA FIKRIYYA (Society for Indonesian Biodiversity, 2020)
Abstract. Helmanto H, Nisyawati, Robiansyah I, Zulkarnaen RN, Fikriyya N. 2020. Habitat preference and spatial distribution model of threatened species Saurauia microphylla in Mt. Slamet, Central Java, Indonesia. Biodiversitas 21: 2946-2954. Saurauia microphylla de Vriese has the potentials for medicinal uses, yet it is listed in the IUCN Red List under Vulnerable status. The natural population of this species is only found in highlands one of which is in Mount Slamet, Central Java, Indonesia. This study aims to determine the population structure, habitat preference and predicted spatial distribution of S. microphylla in the Mount Slamet area. The method used was purposive sampling by establishing 103 observation plots with size of 20x20 m2 for each plot. The research parameters recorded were abiotic variables and biotic associations. Data were analyzed using Principal Component Analysis (PCA) to determine the most influencing environmental factors on the presence of S. microphylla. Species association of S. microphylla was analyzed using the Jaccard index equation. Spatial distribution model was analyzed using Maxent (Maximum Entropy) software. The results showed that S. microphylla populations were found in highland forest areas with elevations of 1689-2265 m above sea level, slope of 3-40°, temperature of 16°-26°C, air humidity of 49.3-90%, soil pH 5.8-7, soil moisture 5-70% and canopy cover of 0-92%. Our analyses revealed that elevation is the most influential factor in the presence of S. microphylla. There are 20 tree species which found around S. microphylla habitat with 4 species have significant association with the species. The spatial distribution model showed that S. microphylla spread across all the slopes of Mount Slamet with the southwestern slope was predicted had the most extensive habitat suitability for the species and become smaller to the north, east, and south slopes.